2023
DOI: 10.1186/s13054-023-04407-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia for accidental hypothermia and increased mortality: a post-hoc analysis of a multicenter prospective observational study

Abstract: Background Supraphysiologic oxygen administration causes unfavorable clinical outcomes in various diseases, including traumatic brain injury, post–cardiac arrest syndrome, and acute lung injury. Accidental hypothermia is a critical illness that reduces oxygen demands, and excessive oxygen is likely to emerge. This study aimed to determine whether hyperoxia would be associated with increased mortality in patients with accidental hypothermia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Body temperature was another important variable in our model, which potentially leads to excessive oxygen molecules that cannot be fully utilized by the tissue. 40 According to its SHAP analysis, lower body temperature was an important predictive factor for 28-d mortality. Regarding laboratory tests, five variables were selected to develop models.…”
Section: Discussionmentioning
confidence: 99%
“…Body temperature was another important variable in our model, which potentially leads to excessive oxygen molecules that cannot be fully utilized by the tissue. 40 According to its SHAP analysis, lower body temperature was an important predictive factor for 28-d mortality. Regarding laboratory tests, five variables were selected to develop models.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown that humans, similar to C. elegans, decrease their whole-body oxygen consumption by half for every 10 °C reduction in temperature, a phenomenon known as the Q10 effect 25 . While the use of anoxia to treat hypothermia has not been attempted to our knowledge, recent analysis has shown that hypothermia patients with hyperoxic arterial oxygen concentrations had a 28-day mortality rate twice that of normoxic patients 26 . Further research to understand if the observations made here extend to other animals and humans may improve our ability to use oxygen concentration and temperature to improve clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Several studies on traumatic brain injury reported that supranormal oxygen suppressed cell metabolism, resulting in neuronal death. 33 Additionally, hyperoxia in the early resuscitation phase was related to increased 28-day mortality risk and/or length of ICU stay among patients with severe injury or accidental hypothermia, 6 34 suggesting that redundant oxygen by hyperoxia may affect tissue or cell metabolism particularly in patients with systemic inflammation, which becomes problematic as organ dysfunction can occur days later rather than during resuscitation. Of note, the incidence of sepsis-related mortality (failure to resuscitation from sepsis) was comparable regardless of hyperoxia exposure in this study.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 However, a supraphysiological amount of oxygen in the blood and/or tissue has been related to unfavourable clinical outcomes in various diseases, including postcardiac arrest syndrome, accidental hypothermia, traumatic brain injury and postcardiac surgery. [3][4][5][6] A recent randomised controlled trial (RCT) on patients receiving mechanical ventilation showed that oxygen titration targeting at 70-100 mm Hg of arterial partial pressure of oxygen (PaO 2 ) reduced the mortality rate in the intensive care unit (ICU). 7 The pathophysiology behind the harmful effects of hyperoxia has been investigated, and oxygen toxicity in the brain and pulmonary tissues affects critically ill patients.…”
Section: Introductionmentioning
confidence: 99%